2016
DOI: 10.1186/s13027-016-0098-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of human Papillomavirus detected among women positive for cervical lesions by visual inspection with acetic acid/Lugol’s iodine (VIA/VILI) in Libreville, Gabon

Abstract: BackgroundThe human papillomavirus (HPV) is the causative agent of cervical cancer, which is the leading cancer-related cause of death for women in Sub-Saharan Africa. In 2013, the Gabonese Ministry of Health and the Sylvia Bongo Ondimba Foundation implemented cervical cancer screening programs based on the detection of cancerous lesions by visual inspection with acetic acid and/or Lugol’s iodine (VIA/VILI). This pilot study was set up to determine the HPV profile and analyze the nucleotide sequence variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
1
16
1
1
Order By: Relevance
“…Several multiple concurrent HPV infections has been reported by numerous studies in particular to Cote d'Ivoire (Jaquet et al, 2010), Benin (Piras et al, 2011), Gabon (Moussavou et al, 2016) and Greece but with rates slightly lower than that obtained in our study. The prevalence of HPV genotypes obtained in our study have also been found by numerous authors in Cote d'Ivoire (Jaquet et al, 2010), within chronological order who obtained HPV 35, HPV 16 and HPV 18.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Several multiple concurrent HPV infections has been reported by numerous studies in particular to Cote d'Ivoire (Jaquet et al, 2010), Benin (Piras et al, 2011), Gabon (Moussavou et al, 2016) and Greece but with rates slightly lower than that obtained in our study. The prevalence of HPV genotypes obtained in our study have also been found by numerous authors in Cote d'Ivoire (Jaquet et al, 2010), within chronological order who obtained HPV 35, HPV 16 and HPV 18.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition, Horo et al (2012) have worked on a population of HIV-infected women and therefore when it is known that HIV infection is a factor in the development of cervical cancer. Elsewhere in Africa, notably in Mali west Africa, Teguete et al (2012) and Moussavou et al (2016) in a similar study in Gabon found in Central Africa have found a high prevalence of precancerous lesions by VIA but in Tanzania, Ngoma et al (2010) found a lower prevalence of precancerous lesions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Participating women were selected from a 960 patient cohort previously constituted from March 2013 to January 2014 during a cervical lesion screening program as part of a multi-center cross-sectional study carried out in two hospitals located in Libreville, Gabon [ 10 ]. A total of 87 women met both main inclusion criteria, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In determining AF estimates for cervical cancer, we identified other African studies that reported the prevalence of HPV in cervical cancer to be between 76% to 91% [16][17][18] . However, an AF of 100% was used for this study since the causality of HPV in cervical cancer is generally known 4,19,20 .…”
Section: Data Handling and Analysismentioning
confidence: 99%